Consequences of hatching deviations for breeding success: a long-term study on blue tits Cyanistes caeruleus. Issue 1 (1st January 2020) - Glądalski, M.; Mainwaring, M. C.; Bańbura, M.; Kaliński, A.; Markowski, M.; Skwarska, J.; Wawrzyniak, J.; Bańbura, J.; Hartley, I. R.
Abstract: The causes and consequences of variation in the incubation regimes of oviparous animals remain unclear, despite having important fitness consequences. Avian incubation regimes can be shortened by parents initiating incubation prior to clutch completion or prolonged when there are gaps in the laying sequence. Here, we begin by quantifying variation in the incubation regimes of three populations of blue tits Cyanistes caeruleus from the UK and Poland before examining the consequences of such variation for their hatching and fledging success. We then investigate the mechanism causing such variation by exploring the impact of local weather conditions on incubation regimes. The difference between the expected and actual hatching dates of clutches was termed the "hatching deviation" and this showed considerable variation. Hatching deviation was negatively related to local temperature and clutch size. Hatching deviation affected hatching success and hatching deviation, temperature, wind speed and clutch size affected fledging success. Deviating from the expected laying and incubation regime caused lowered reproductive success. The most successful birds were those that were able to lay one egg per day and begin incubation upon clutch completion.